Implementasi Kebijakan Pengelolaan Lingkungan Hidup pada Kegiatan Penambangan Intan di Kecamatan Cempaka, Banjarbaru - Decky Kuncoro; Ahmad Jamaluddin Islami; Beni Akhmad (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2025)
Diamond mining in Cempaka District, Banjarbaru, significantly contributes to the local economy but also causes adverse environmental impacts. This study aims to assess the implementation of environmental management policies in diamond mining activities in the area and identify the factors hindering their implementation. The research uses a qualitative approach with in-depth interviews of key stakeholders, including local government, community members, and miners. The findings reveal that although environmental management policies have been implemented, key challenges such as weak law enforcement, lack of community participation, and limited resources for supervision hinder their effectiveness. Environmental impacts include land degradation, reduced water quality, and threats to biodiversity. The study recommends improving supervision, enforcing stricter laws, and raising community awareness and involvement in environmental management processes.